The effect of organic compost of Caryocar brasiliense waste against Meloidogyne javanica in two vegetable crops - Silva, Fabíola De J.; Ribeiro, Regina C.F.; Xavier, Adelica A.; Gomes, Vanessa A. [UNESP]; Pacheco, Paulo V.M.; Neto, José A. Dos S. (De Gruyter, 2021)
Root-knot nematodes (Meloidogyne spp.) are responsible for various significant crop losses, which require taking integrated control measures. The present study aimed to identify a possible sustainable approach to the management of Meloidogyne javanica in vegetable crops using an organic compound based on pequi (Caryocar brasiliense) fruit residues. A pot experiment was conducted using cultivars of tomato and lettuce susceptible to M. javanica, with three amendments including inorganic fertiliser, cattle manure and five doses of organic compost with pequi residues. All treatments were inoculated with second-stage juveniles of M. javanica to simulate the root-knot nematode disease in field conditions. Increasing doses of organic compost with pequi residues from 5 kg m-3 to 30 kg m-3 promoted a significant decrease in the nematode population in both cultures evaluated. Organic compost (30 kg m-3) reduced the numbers of galls and eggs of M. javanica by 41.6 and 46.5% in tomato roots, and by 80.3 and 59.2% in lettuce roots, respectively, compared with non-treated control. Organic compost also increased crop development considerably. In general, there was a 43.0% increase in plant development compared to non-treated control. Hence, organic compost of pequi residues could be an alternative to toxic chemical nematicides and recommended as eco-friendly management of M. javanica in vegetable crops.
Keywords: alternative control; lettuce; management; organic amendments; pequi; root-knot nematode; tomato